The effects of steroid implant and dietary soybean hulls on estrogenic activity of sera of steers grazing toxic endophyte-infected tall fescue pasture - Shappell, Nancy W.; Flythe, Michael D.; Aiken, Glen E. (Frontiers in Veterinary Science, 2015)
Soybean hulls (SBHs) have been fed to cattle pasturing on endophyte-infected tall fescue in attempts to increase rate of gain. Literature reports indicated some symptoms associated with fescue toxicosis were ameliorated by the use of steroidal implants containing estradiol (E2) and progesterone (IMP), feeding SBHs, or the combination of the two. While the mechanism for amelioration was unclear, the SBHs were postulated as acting as a diluent of the toxic factors of the fescue. Alternatively, estradiol and phytoestrogens of SBHs might be acting through relaxation of the persistent vasoconstriction found in animals ingesting ergot alkaloids of endophyte-infected fescue. If so, estrogenic activity of serum of steers receiving SBHs, IMP, or a combination of the two should be elevated. Using the cellular proliferation assay of estrogenicity (E-Screen), estradiol equivalents (E2Eqs) were determined on both SBHs and the serum of steers from a previously reported study. Range of SBHs was 5.0 to 8.5 ng Eqs g-1 DM (mean 6.5, n=4 different commercial sources of SBHs). At the rate fed, theoretical calculated blood E2Eq could be physiologically relevant (~ 80 pg mL-1, based on 2.3 kg SBHs d-1, 300 kg steer, 5.7% blood volume, and 10% absorption). Serum E2Eqs did increase in steers (P ≤ 0.05) with steroidal implants or fed SBHs by 56 and 151% over control respectively, and treatments were additive (211% increase). Serum prolactin was also greatest for the SBH+IMP group (188 ng mL-1, P < 0.05), concentrations comparable to values reported for steers grazing endophyte-free fescue. Prolactin in the SBH group was higher than IMP or control groups (146 vs 76 and 60 ng mL-1, respectively). Still unknown is if additional E2Eqs from dietary phytoestrogens or exogenous sources of estradiol can further reduce symptoms of fescue toxicosis. The E-Screen assay was an effective tool in monitoring serum for estrogenic effects of dietary supplementation with SBHs or estrogenic implants.